Factors influencing the participation of adolescents and young adults with a congenital heart disease in a transition education program: A prospective multicentre controlled study. Issue 12 (December 2019) - Werner, Oscar; Abassi, Hamouda; Lavastre, Kathleen; Guillaumont, Sophie; Picot, Marie-Christine; Serrand, Chris; Dulac, Yves; Souletie, Nathalie; Acar, Philippe; Bredy, Charlene; Amedro, Pascal
Highlights: Many young adults with congenital heart disease (CHD) interrupt their follow-up. Transition education programs aim to facilitate transfer to adult cardiology. Transition education programs intend to bring more autonomy to teenagers. Poor disease knowledge and risk behaviours are risk factors. Many risk factors are controllable. Abstract: Objective: Transition education programs dedicated to adolescents and young adults with congenital heart disease (CHD) aim to facilitate transfer to adult cardiology and bring more autonomy to teenagers. This prospective controlled multicentre study analysed the factors influencing the participation in a transition education program. Methods: CHD patients aged 13–25 y were offered to participate in the transition program. A multiple linear regression identified the explanatory factors for participation in the program. Results: A total of 123 patients (mean age 19.6 ± 3.4 y) were included in the study, with 57 participants and 66 non-participants. Both groups showed similar socio-demographic and quality of life characteristics, low level of physical activity with muscular deconditioning and high exposure to risk behaviours (71% patients with ≥1 risk factor). Patients with complex CHD (OR = 4.1, P = 0.03), poor disease knowledge (OR = 0.3, P = 0.02), risk behaviours (body piercing, OR = 5.53, P = 0.01; alcohol, OR = 3.12, P = 0.06), and aged <20 y (OR = 0.29, P = 0.03), were more likely to join the program. Conclusion: Many risk factors influencing the participation of adolescents and young adults with CHD in transition education programs are controllable. Practice implication: Further randomized studies are necessary to evaluate the impact of transition education program on quality of life, successful transfer to adult centre and, ultimately, prognosis.